Performance optimizing of pneumatic soft robotic hands using wave-shaped contour actuator - Hui Chen; Mohammed A.H. Ali; Zhenya Wang; Junlong Chen; Montaser N.A. Ramadan; Mohammad Alkhedher (Results in Engineering)
Soft robotic hands have gained significant attention in recent years due to their simplicity in control, ease of fabrication, and remarkable compliance. However, traditional designs often suffer from limited contact area and insufficient grasping force. In this study, we propose a novel four-finger pneumatic soft robotic hand with wave-shaped contour actuators to address these issues. Inspired by natural grasping mechanisms, the proposed design integrates multiple actuation modes to enhance both adaptability and reliability. An analytical model based on constant curvature bending theory and the Yeoh constitutive model is developed to guide the design and predict the performance of the actuators. The model is validated through extensive Abaqus finite element simulations, demonstrating excellent agreement with experimental results. Our findings confirm that the actuators achieve consistent and reliable bending motion with optimal structural parameters. Experimental evaluation of the soft robotic hand includes bending trajectory analysis and grasping tests with various irregular objects. The results show that the actuators provide a maximum bending angle of 180° under 26 kPa pressure and maintain stable grasps for objects of different shapes and sizes. The soft robotic hand demonstrates superior grasping adaptability and reliability due to its high compliance and optimized design. This study paves the way for practical applications in industrial automation, medical devices, and service robotics, highlighting the potential of wave-shaped contour actuators in enhancing the functionality of soft robotic hands.